Factors Influencing Internet Addiction Among University Students: A Review - Sidek, Safiah; Kudus, Norliah; Izharrudin, Siti Zakiah; Kamalrudin, Massila; Abu Hassan, Mahadi; Mohamed , Shahrulanuar (Publications International, 2016)
The widespread usage of Internet worldwide has resulted in a tremendous change in people’s lifestyle, particularly the young generation, which is recognized as the digital natives. However, there is an increased concern in the use of Internet among university students as they can become addicted to Internet due to its excessive usage. In this respect, it is vital to investigate the pattern of Internet usage of the users as the ways in which they use Internet may result in the Internet addiction. Considering that Internet addiction can disrupt the productivity of a nation, extensive studies of Internet addiction have been conducted, and most of these studies were conducted in countries that have advanced technology of Internet. This paper presents a review of the existing studies of the factors contributing to Internet addiction among university students. Based on the review, these factors can be categorized into four factors, namely, the psychological factors, demographic factors, socioeconomic factors and usage pattern. Drawn from this review, a conceptual framework consisting of eight factors influencing Internet addiction has been formulated. This conceptual framework serves as a research design to investigate the factors that influence Internet addiction among university students.